The function of nasal pressure for breathing in the breaststroke - Hara, H.; Watanabe, R.; Hanaki, A.; Shibata, Y.; Yamamoto, Y.; Onodera, S. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this paper is to discuss the function of the Sensation of water touching the face and the effects of nasal pressure on breaststrokers. For examining facial Sensation, skin around the nose was covered with film. To study effects of nasal pressure, the nostril was covered with film. Then the pressure data and other data were analyzed using the Student T-test. There was no difference (t =0.40) in depth pressure with swimmers covered with film and not covered. When the nostrils were closed, face depth (average: 30.3cm) was shallower (t=0.006) than in the controlled setting (28.0cm). There were no significant differences (t=0.62) between the experimental and controlled settings with regards to face-sustaining duration above water surface and subjects' breathing.